Agaricus bisporus mushroom as partial fat replacer improves the sensory quality maintaining the instrumental characteristics of beef burger - Patinho, Iliani (2021)
Iliani Patinho is grateful to CAPES (Coordenação de Aperfeiçoamento de Pessoal de Nível Superior, Brazil, for the master scholarship (process n° 1766129). Juan D. Rios-Mera received the support of the CIENCIACTIVA programme, PhD scholarship contract n° 238-2018-FONDECYT. The authors would also like to thank Zucca mushrooms Company, VPJ Foods, Ibrac Additives and Condiments and Sealed Air Brazil, for donating ingredients, raw materials and packaging.